2014
DOI: 10.1002/jcop.21661
|View full text |Cite
|
Sign up to set email alerts
|

Counterspaces and the Narrative Identity Work of Offender‐labeled African American Youth

Abstract: Through narrative identity work, offender‐labeled African American youth craft positive self‐concepts in the face of denigrating societal messages about their personhood. While past research suggests narrative identity work is largely intrapersonal, recent theory posits that it may also arise through individuals’ participation in counterspaces. This 9‐month ethnography explored how a group of offender‐labeled African American youth engaged in narrative identity work through participation in an intervention pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 36 publications
2
47
0
Order By: Relevance
“…Participants mentioned laughing with staff and staff accepting their individuality and granting opportunities to experience a sense of freedom. In our findings, participants reflect what Case and Hunter () described as self‐enhancing processes, where they have opportunities to reduce emotional tension in prosocial ways.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Participants mentioned laughing with staff and staff accepting their individuality and granting opportunities to experience a sense of freedom. In our findings, participants reflect what Case and Hunter () described as self‐enhancing processes, where they have opportunities to reduce emotional tension in prosocial ways.…”
Section: Resultssupporting
confidence: 74%
“…Case and Hunter (2014) suggest adult relationships can 'facilitate adaptive responding' (p. 261) by transmitting the cognitive strategies young people need to buffer attacks against their selfconcept. Young people who are able to develop strong relational and emotional ties with adults receive reinforcement and are able to build a positive sense of self and efficacy towards accomplishing tasks (Case and Hunter, 2014;Ginwright, 2007;Whitlock, 2007). A study conducted by Jones and Deutsch (2011) demonstrated that positive adult relationships allow young people to project a more favourable future orientation and aspirations.…”
Section: Social Connectedness In Spaces Of Recoverymentioning
confidence: 99%
“…This language redefines homelessness from the consequence of excessive permissiveness and a lack of regulation to the concentration of wealth and erosion of the public due to privatization. Such findings contribute to a growing body of literature highlighting the importance of resistance narratives for marginalized groups in contesting stigmatizing dominant narratives, affirming their dignity and worth, and claiming equal rights (see Case and Hunter 2014;Opsal 2011;Sonn and Fisher 1998).…”
Section: Discussionmentioning
confidence: 62%
“…A small but notable body of community psychology scholarship has examined various strategies for resisting dominant cultural narratives, such as the deconstruction of social myths as a central part of critical consciousness raising (Sonn & Fisher, 2003), and the telling of counter-narratives, re-imagined narratives of the self that reject the assumptions of dominant cultural narratives, and emphasize the capacity to resist and overcome oppression (Case & Hunter, 2012;McDonald et al, 2007;Rappaport, 2000). Much of this work signals the importance of identity-focused strategies for negotiating dominant cultural narratives, and points toward a broader body of scholarship on identity work (more recently referred to as narrative identity work), which is concerned with the construction and strategic use of personal and collective identity through narrative (Case & Hunter, 2014;Ibarra & Barbulescu, 2010;Snow & Anderson, 1987). Studies have shown that marginalized people use various forms of identity work to negotiate oppression.…”
Section: Resistancementioning
confidence: 99%